Kajian mengenai dialog dua hala sebagai pendekatan Qurani dalam tilawah al-Quran - Abd. Latif Mohd. Abdul Nasir, Abd. Hadi Ahmad Zulfiqar Shah, Mohd Yusof Mohd Yakub @ Zulkifli, (N/A, 2014)
Kajian mengenai dialog dua hala sebagai pendekatan Qurani dalam tilawah al-Quran by Abd. Latif Mohd. Abdul Nasir, Abd. Hadi Ahmad Zulfiqar Shah, Mohd Yusof Mohd Yakub @ Zulkifli,